Clinical, laboratory and health-related quality of life correlates of Systemic Lupus Erythematosus Responder Index response: a post hoc analysis of the phase 3 belimumab trials. Issue 1 (27th June 2014) - Furie, Richard; Petri, Michelle A; Strand, Vibeke; Gladman, Dafna D; Zhong, Z John; Freimuth, William W
Abstract : Objective: Correlates of systemic lupus erythematosus (SLE) Responder Index (SRI) response with clinical trial end points were examined using pooled data from the Study of Belimumab in Subjects with SLE (BLISS) trials (N=1684). Methods: Changes in clinical, laboratory and health-related quality of life measures from baseline at 52 weeks were compared between SRI responders (n=761) and non-responders (n=923). Results: More SRI responders than non-responders had ≥4-point (100% vs 3.8%) and ≥7-point (40.3% vs 1.3%) Safety of Estrogens in Lupus Erythematosus National Assessment-Systemic Lupus Erythematosus Disease Activity Index reductions, no new British Isles Lupus Assessment Group (BILAG) A and ≤1 new B scores (91.9% vs 35.9%), and a 25% reduction in corticosteroid dose decrease of 25% from >7.5 mg/d to ≤7.5 mg/d (25.5% vs 13.9%), and fewer had a corticosteroid increase from ≤7.5 mg/d to >7.5 mg/d (4.1% vs 21.3%; all p<0.001). More responders than non-responders had improved organ domains: Safety of Estrogens in Lupus Erythematosus National Assessment-Systemic Lupus Erythematosus Disease Activity Index (mean 1.45 vs 0.40), BILAG (2.00 vs 0.39), and greater improvement in Physician's Global Assessment (all p<0.001). Risks for developing any SLE flare or severe flare were reduced in responders by 42% and 87%, respectively (p<0.001). Responders reported greater improvements in Medical Outcomes Survey Short Form version 2 Physical and Mental Components and all domain scores, and Functional Assessment of Chronic Illness Therapy-Fatigue score compared with non-responders (all p<0.001). Conclusion: Overall, SRI response in patients with active, autoantibody-positive SLE was associated with improvements in clinical, laboratory and patient-reported outcome measures, indicating that SRI response was associated with a global benefit. Trial registration number: NCT00424476; NCT00410384 .